Clinicians' strategies for managing their emotions during difficult healthcare conversations. Issue 9 (September 2016) - Luff, Donna; Martin, Elliott B.; Mills, Kelsey; Mazzola, Natalia M.; Bell, Sigall K.; Meyer, Elaine C.
Highlights: Clinicians report various strategies to manage emotions in difficult conversations. Five categories of strategies were identified. Self-care strategies were the most commonly reported. Strategies extend to periods before, during, and after difficult conversations. Existing strategies may help to inform future educational interventions. Abstract: Objectives: To examine strategies employed by clinicians from different disciplines to manage their emotions during difficult healthcare conversations. Methods: Self-report questionnaires were collected prior to simulation-based Program to Enhance Relational and Communication Skills (PERCS) workshops for professionals representing a range of experience and specialties at a tertiary pediatric hospital. In response to an open-ended prompt, clinicians qualitatively described their own strategies for managing their emotions during difficult healthcare conversations. Results: 126 respondents reported emotion management strategies. Respondents included physicians (42%), nurses (29%), medical interpreters (16%), psychosocial professionals (9%), and other (4%). Respondents identified 1–4 strategies. Five strategy categories were identified: Self-Care (51%), Preparatory and Relational Skills, (29%), Empathic Presence (28%), Team Approach (26%), and Professional Identity (20%). Conclusions: Across disciplines and experience levels, clinicians have developed strategies to manage their emotions when holding difficult healthcare conversations. These strategies support clinicians before, during and after difficult conversations. Practice implications: Understanding what strategies clinicians already employ to manage their emotions when holding difficult conversations has implications for educational planning and implementation. This study has potential to inform the development of education to support clinicians' awareness of their emotions and to enhance the range and effectiveness of emotion management during difficult healthcare conversations.